The Corporate Liability of Airline Service Business Actors in Indonesia: An Islamic Law Perspective - Hartono, Teguh; Hartiwiningsih, Hartiwiningsih; Suwadi, Pujiono (Unissula, 2024)
This study aims to analyze the weaknesses of the corporate liability arrangements of airline service business actors for consumer protection in the perspective of Islamic law in Indonesia. Legal research in the form of prescriptive, with statutory, case, conceptual and comparative approach. Comparative legal studies were conducted with Malaysia, Singapore and Australia supported by the theory of maqashid shariah, welfare state theory and justice theory. The research shows that; First, there are weaknesses in the regulation of liability of business actors in the Consumer Protection Law and the Aviation Law, which have not been able to reach the liability. Beside that, it is not fulfilled the principle of Al-adl because of justice, balance, and equality that describe the horizontal dimension. Second, there is prescription for future arrangements in the corporate liability of airline business actors in the perspective of Islamic law. The position of consumers and business actors should be equal based on the maqashid shariah. Aviation Service Business Actors must be responsible for consumer losses whose rights are violated as regulated in the Qur'an and Hadith. Based on the principle of Al-adl in maqashid shariah, it is necessary to reconstruct the regulation of aviation law and consumer protection law.